PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP INTENTION TO LEAVE PADA KARYAWAN PRODUKSI MITRA PRODUKSI SIGARET (MPS) NGORO-JOMBANG - Rini Ratna Nafita Sari (University of Merdeka Malang, 2017)
The purpose of this study was (1) to analyze the effect of job satisfaction on organizational commitment, (2) analyze the effect of job satisfaction on intention to leave, (3) analyze the effect of organizational commitment on intention to leave, (4) analyze the effect of job satisfaction on intention to leave through organizational commitment. This research was conducted by using path analysis (Path analys). Data on job satisfaction, organizational commitment, and intention to leave was obtained through interviews and using a questionnaire distributed to 90 respondents MPS Ngoro JOMBANG employee who is a partner of PT.Hm. Sampoerna Tbk. From the research variables that affect the intention to leave, namely job satisfaction variables significantly positive effect on organizational commitment, job satisfaction variables were not significant negative effect on intention to leave, organizational commitment variables significantly influence the intention to leave, and organizational commitment variables moderating the effect of job satisfaction on intention to leave.